2019
DOI: 10.1021/acs.jctc.9b00474
|View full text |Cite
|
Sign up to set email alerts
|

Protein Docking Using a Single Representation for Protein Surface, Electrostatics, and Local Dynamics

Abstract: Predicting the assembly of multiple proteins into specific complexes is critical to understanding their biological function in an organism and thus the design of drugs to address their malfunction. Proteins are flexible molecules, which inherently pose a problem to any protein docking computational method, where even a simple rearrangement of the side chain and backbone atoms at the interface of binding partners complicates the successful determination of the correct docked pose. Herein, we present a means of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…To test the feasibility of dimer occurrence, we further explored the bo 3 dimer structure using protein-protein docking in conjunction with molecular dynamics. 20 We simulated the monomer (PDB: 1FFT) 21 in a 1-palmitoyl-2-oleoyl-glycero-3-phosphocholine (POPC) bilayer for 60 ns, and used this equilibrated structure to generate a pool of possible dimeric arrangements (best candidate is shown in Figure 2C). We then calculated the transmembrane solvent-accessible surface area (SASA) of monomeric bo 3 (21,800 Å 2 ).…”
Section: Detergent and Apol Solubilized Impsmentioning
confidence: 99%
“…To test the feasibility of dimer occurrence, we further explored the bo 3 dimer structure using protein-protein docking in conjunction with molecular dynamics. 20 We simulated the monomer (PDB: 1FFT) 21 in a 1-palmitoyl-2-oleoyl-glycero-3-phosphocholine (POPC) bilayer for 60 ns, and used this equilibrated structure to generate a pool of possible dimeric arrangements (best candidate is shown in Figure 2C). We then calculated the transmembrane solvent-accessible surface area (SASA) of monomeric bo 3 (21,800 Å 2 ).…”
Section: Detergent and Apol Solubilized Impsmentioning
confidence: 99%
“… 21 GROMACS 22 is then used to generate the simulation data using the Amber14SB 23 and SLipid 24 force fields, which enables the generation of STID maps. The maps of both binding partners are then converted into isosurfaces using a predetermined cutoff and docked such that their surface complementarity is maximized 16 (see SI and Figure S2 ). This surface-based scoring function is effective because it bypasses the need to explicitly handle packing of interfacial atoms, yielding smoother and gentler gradients compared to typical atomistic representations (see SI and Figure S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some proteins can form multiple complexes by interacting with different binding partners. In our previous work, 16 we observed that knowledge of a protein’s bound state with a specific partner may facilitate its docking with a different one; i.e., the bound state of the native complex from which the ligand or receptor is sourced can be used as a surrogate for the target complex. Here, we tested this approach with the 1M56 test case, comprised of two binding partners that have had their structures solved as part of an alternative complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most basic approaches, the protein is simply seen as a surface, which is enhanced by electrostatic properties [7] . Such approaches are still in use for protein–protein docking, where a more complex representation is not feasible [8] . In protein-ligand docking, the selected binding site is represented in more detail.…”
Section: Structure-based Computational Methodsmentioning
confidence: 99%